Impairment of quality of life in parents of children and adolescents with pervasive developmental disorder - Mugno, Diego (BioMed Central, 2007)
BACKGROUND: Little is known about the Quality of Life (QOL) in parents of children with developmental diseases as compared to other severe neurological or psychiatric disorders. Aims of the present study were: to evaluate QOL in parents of children affected by Pervasive Development Disorder (PDDs), Cerebral Palsy (CP) or Mental Retardation (MR) as compared to a control group (CG); to evaluate QOL of parents of patients with different types of PDDs, namely Autistic Disorder (AD), High Function Autism/Asperger Syndromes (HFA/AS) and Pervasive Developmental Disorder Not Otherwise Specified (PPD-NOS); and to compare the level of impairment in QOL of mothers and fathers within PDDs, CP, MR groups and between AD, HFA/AS, PDD-NOS sub-groups. METHODS: The sample consisted of 212 parents (115 mothers and 97 fathers) of 135 children or adolescents affected by PDDs, MR or CP. An additional sample of 77 parents (42 mothers and 35 fathers) of 48 healthy children was also included and used as a control group. QOL was assessed by the WHOQOL-BREF questionnaire. RESULTS: Compared with parents of healthy children, parents in the PDDs group reported impairment in physical activity (p = 0.0001) and social relationships (p = 0.0001) and worse overall perception of their QOL (p = 0.0001) and health (p = 0.005). Scores in the physical (p = 0.0001), psychological (p = 0.0001) and social relationships domains (p = 0.0001) and in the physical (p = 0.0001) and social relationships (p = 0.0001) domains were lower compared to the MR group CP group respectively. Little differences were observed between MR, CP and control groups. The level of impairment of physical (p = 0.001) and psychological (p = 0.03) well-being were higher in mothers than in fathers in the PDDs and CP groups respectively; in the other groups, and across all the other domains of QQL impairment was similar. There were no statistically significant differences in the scores between the AD, HFA/AS and PDD-NOS sub-groups, but parents in the HFA/AS sub-group seemed to display a lower QOL compared to the AD sub-group. CONCLUSION: Parents of children with PDDs seem to display a higher burden, probably for a combination of environmental and genetic factors. Within this group of parents also those of HFA or AS people have higher stress. These finding must be taken into account in policy making to provide better and more specific supports and interventions for this group of diseases.